Groundwater Filtration Monitoring System with IOT-based Water Clarity Parameters using Node Red (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Groundwater quality, as the primary source of domestic needs, often experiences fluctuations in turbidity levels, which affect its suitability. Conventional filtration systems commonly used by the public have weaknesses in monitoring aspects, where checking water conditions and filter saturation is still done manually and not in real time. This research aims to design a monitoring system for the quality of groundwater filtration results based on the Internet of Things (IoT), focusing on water clarity parameters. This system is designed using a turbidity sensor to detect turbidity levels in NTU (Nephelometric Turbidity Unit) units integrated with a microcontroller as a data processing unit. The sensor data is then transmitted via the internet network to a server for processing and visualization. Node-RED is used as the main platform to build a user interface monitoring dashboard. The research methods include hardware design, software development, and testing of sensor reading accuracy and system responsiveness. The test results show that the system is able to read water turbidity values ​​accurately with an average sensor reading error percentage of 2 percent and displays data in real-time on the Node-RED dashboard in the form of graphs and status indicators. The implementation of this system makes it easier for users to monitor water quality remotely and determine filter maintenance times more precisely.